Penerapan Sistem Penjaminan Mutu Internal pada Pekan Kewirausahaan Unit Entrepreunership Laboratorium Terpadu - Mail Hilian Batin; Dika Setiagraha; Ilham Prawidi Sakti (Journal of Trends Economics and Accounting Research, 2023)
The Internal Quality Assurance System is a systemic activity of education quality assurance by universities to supervise the implementation of higher education by the universities themselves on an ongoing basis. The word supervise means 'planning', 'implementation', 'control', and 'development / improvement' of higher education quality standards consistently and continuously for stakeholder satisfaction. In this study, the application of SPMI was carried out in the Entrepreneurship Week program with the hope that it could carry out quality quality. The presence of laboratories in universities is important as a place for students to experiment in the teaching and learning system. Material about Entrepreneurship is always taught to students, but only fixated on assignments but not yet economically valuable. There is an entrepreneurship week program as a forum for students to be creative in selling their products to a wide audience and is always evaluated by the laboratory if there are obstacles in the field. This type of research is a field research with a qualitative descriptive approach. The results showed that the establishment of an internal quality assurance system, especially for the Entrepreneurship Unit as a reference for the implementation of the Entrepreneurship Week program in the future.